Status of Targeting MreB for the Development of Antibiotics - Awuni, Elvis (Frontiers in Chemistry, 2020)
Although many prospective antibiotic targets are known, bacterial infections and resistance to antibiotics remain a threat to public health partly because the druggable potentials of most of these targets have yet to be fully tapped for the development of a new generation of therapeutics. The prokaryotic actin homolog MreB is one of the important antibiotic targets that are yet to be significantly exploited. MreB is a bacterial cytoskeleton protein that has been widely studied and is associated with the determination of rod shape as well as important subcellular processes including cell division, chromosome segregation, cell wall morphogenesis, and cell polarity. Notwithstanding that MreB is vital and conserved in rod-shaped bacteria, no approved antibiotics targeting it are presently available. Here, the status of targeting MreB for the development of antibiotics is concisely summarized. Expressly, the known therapeutic targets and inhibitors of MreB are presented, and the way forward in the search for a new generation of potent inhibitors of MreB briefly discussed.